APPLICATION OF REJECTED WAX APPLE FRUIT AS A BIO-CATALYTIC PHYTOACTIVATION (BCP) AGENT IN THE CULTIVATION OF MIMUSOPS ELENGI - Markani Markani; Raden Muhammad Idris; Ananta Ria Safitri; Sevina Ayu Andini (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
In the conservation area, the growth of tanjung trees (Mimusops elengi) was found to be suboptimal due to low soil nutrient availability, limited microbial activity, and compact soil structure with poor porosity. In addition, there was an environmental issue related to the underutilization of rejected or rotten wax apple fruits (jambu air afkir), which have the potential to generate unpleasant odors and greenhouse gas emissions through open decomposition. To address these challenges, an innovation was introduced by converting rejected wax apple waste into liquid organic fertilizer (LOF) and compost, which function as biocatalysts to improve soil fertility and support the growth of tanjung trees. The study employed a before-and-after experimental approach (pre-test and post-test). The results showed that the company successfully planted 100 tanjung seedlings and processed approximately 80–120 kg of rejected wax apple waste per month into organic fertilizer products. Meanwhile, community members actively participated in collecting and sorting approximately 50–80 kg of rejected wax apple waste per month, enhanced their skills in organic fertilizer production, and gained the potential to reduce fertilizer expenses by approximately 20–30% for household gardens and small-scale farming activities. This finding indicates that rejected wax apple fruit waste can be utilized as liquid organic fertilizer and compost. This application can help promote vegetative growth in plants, resulting in growth of approximately 4 cm/month. Furthermore, it provides environmental, economic, and social benefits to the surrounding community. This effort represents an integrated solution to address two challenges simultaneously: organic waste management and suboptimal plant growth.